Feasibility Reconstruction of Kumbasari Park as a Tourism Attraction - I Nyoman Sunarta; I Made Trisna Semara; I Made Sudjana; Angelina Hartono (International Journal of Social Science and Business, 2023)
Kumbasari Park has been proven to have a fairly good level of tourist friendliness. However, this is not enough to make Kumbasari Park a tourist attraction in Denpasar. Even though its existence has been in tune with the tourism concept of Denpasar, which is heritage tourism. Therefore, this study was conducted to figure out whether Kumbasari Park is suitable as a tourist attraction or not by reviewing the implementation of the rights, obligations, and prohibitions that have been stated in Law Number 10 of 2009 concerning Tourism. This research was conducted with a qualitative descriptive approach using direct observation and documentation to collect the data. Furthermore, the result of the observation was adjusted to the list of articles 19 to 27 in Law Number 10 of 2009 concerning Tourism. Based on the observation and data collected, it was found that Kumbasari Park should have been classified as a representative tourist attraction through the perspective of implementing rights, obligations, and prohibitions according to Indonesia’s tourism law. However, there are still some further improvements that need to be made by the management of Kumbasari Park.